Flexural and compressive behaviour of I steel section strengthened by stainless steel plate. (2022) - Kavitha, R.; Sundarraja, M.C.; Indhiradevi, P.; Manikandan, P.; Archana vaishnavi, S.; Karthikeyan, G.; Rahman, A. Abdul; Akash, E.
Abstract: Because of its great mechanical, durability, and aesthetic features, stainless steel is commonly utilised in construction. Stainless steel is likely to become increasingly widely specified in the building of sustainable infrastructure. This research looks at the experimental and analytical study of the flexural and compressive behaviour of steel sections strengthened with duplex stainless steel. The ISMB125 section is arc welded using duplex stainless steel plate of various thicknesses and lengths. Using a standard loading frame test, a standard 3-point bending and axial compressive test is performed, with the results revealing the load–displacement, ultimate load, stress, and strain. Following the experimental research, all of the specimens were analysed using the finite element method in ANSYS, with the results compared to those obtained experimentally. The optimal length and thickness of stainless steel plates for strengthening steel beams and columns are determined.